JANDO BERAES SEBAGAI KONTEKS PEMBELAJARAN BERBASIS PENDEKATAN PMRI PADA MATERI ARITMATIKA SOSIAL - Desvitasari, Tria; Zulkardi, Zulkardi; Susanti, Ely; Meryansumayeka, Meryansumayeka (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2024)
Social arithmetic is one of the mathematics learning materials that is very important and close to students' lives. This material is often considered easy, but in fact, students often face difficulties in understanding social arithmetic, especially in profit/loss material. With this condition, we must be able to compile a learning that is fun, interesting and directly involved in learning, including by using the PMRI approach. The research method used in this study is design research type validation studies, which consists of 3 stages, namely preparation and design, design experiment and retrospective analysis. This study formulates the Hypothetical Learning Trajectory (HLT) into 4 (four) activities, namely: (1) product design activities to determine the purchase price; (2) the activity of making products to determine the selling price; (3) the activity of selling products to determine profit/loss; (4) mathematical problem solving activities regarding profit/loss. The data collection technique in this study uses observation, voice recordings and LAS then analyzed descriptively, which is seen from the results of observations in the classroom, namely comparing HLT and the learning activity process. The result of this study is that the learning trajectory designed to increase the understanding of in-depth concepts about social arithmetic is in accordance with the characteristics of PMR learning, namely the use of context, the use of models, student engagement, interactivity and connection with other learning materials.